2004
DOI: 10.1016/j.neuron.2004.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Integration of Looming Signals by Rhesus Monkeys

Abstract: Looming objects produce ecologically important signals that can be perceived in both the visual and auditory domains. Using a preferential looking technique with looming and receding visual and auditory stimuli, we examined the multisensory integration of looming stimuli by rhesus monkeys. We found a strong attentional preference for coincident visual and auditory looming but no analogous preference for coincident stimulus recession. Consistent with previous findings, the effect occurred only with tonal stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
144
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(165 citation statements)
references
References 33 publications
19
144
2
Order By: Relevance
“…The multisensory interaction demonstrated in our study almost certainly does not arise from sensory-neural convergence of auditory and visual signals, i.e., the kind of convergence that has been well-established in single-cell sensory neurophysiology (51)(52)(53) and in human brain imaging (54). Instead, the interactions implicated in our study more likely entail information combination of the sort discussed in the context of cue combination across modalities (55,56).…”
Section: Discussionsupporting
confidence: 47%
“…The multisensory interaction demonstrated in our study almost certainly does not arise from sensory-neural convergence of auditory and visual signals, i.e., the kind of convergence that has been well-established in single-cell sensory neurophysiology (51)(52)(53) and in human brain imaging (54). Instead, the interactions implicated in our study more likely entail information combination of the sort discussed in the context of cue combination across modalities (55,56).…”
Section: Discussionsupporting
confidence: 47%
“…Ethologically, a role in alertness for dangerous stimuli is highly probable, an interpretation that can also be attributed to the visuo-somatosensory projections: the specific link between the FST visual complex and the representation of the face in the somatosensory cortex could contribute to phenomena of avoidance of a ''dangerous" stimulus which may hit the body Graziano, 2003, 2004). More recently, there is also evidence for selective interactions between auditory-visual cues signaling approach or looming (Maier et al, 2004(Maier et al, , 2008Cappe et al, 2009b).…”
Section: Specificity Of Heteromodal Connections: Ethological Rolementioning
confidence: 99%
“…Prior studies have reported results for a variety of auditory phenomena including intensity discrimination ͑Schlauch et al, 1998͒, subjective duration ͑DiGiovanni and Schlauch, 2007;Grassi and Darwin, 2006;Schlauch et al, 2001a, 2001b͒, loudness ͑Irino and Patterson, 1996Neuhoff 1998Neuhoff , 2001Maier et al, 2004;Stecker and Hafter, 2000͒, and tonality ͑Patterson, 1994a. All of these studies, except that on intensity discrimination ͑Schlauch et al, 1998͒, report perceptual differences between ramped and damped stimuli of the same physical duration.…”
Section: Introductionmentioning
confidence: 99%